2019
DOI: 10.1159/000495360
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness through the Dental-Health FRAMM Guideline for Caries Prevention among 12- to 15-Year-Olds in Sweden

Abstract: Since 2008, FRAMM has been a guideline for caries prevention for all 3- to 15-year-olds in the Västra Götaland Region in Sweden and a predominant part is school-based fluoride varnish applications for all 12- to 15-year-olds. The aims were to evaluate dental health-economic data among 12- to 15-year-olds, based on the approximal caries prevalence at the age of 12, and to evaluate cost-effectiveness. Caries data for 13,490 adolescents born in 1993 who did not take part and 11,321 adolescents born in 1998 who fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(31 citation statements)
references
References 17 publications
(7 reference statements)
2
27
0
2
Order By: Relevance
“…Of the 26 included studies, ten were economic evaluations directly based on empirical studies [19][20][21][22][23][24][25][26][27][28] and the other 16 were modelling studies [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. In nine studies, the target population comprised pre-school children up to five years of age [19,22,25,26,31,32,35,36,38].…”
Section: Study Findingsmentioning
confidence: 99%
“…Of the 26 included studies, ten were economic evaluations directly based on empirical studies [19][20][21][22][23][24][25][26][27][28] and the other 16 were modelling studies [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. In nine studies, the target population comprised pre-school children up to five years of age [19,22,25,26,31,32,35,36,38].…”
Section: Study Findingsmentioning
confidence: 99%
“…A total of 738 articles were initially identified and reviewed and 15 met the inclusion criteria 16‐30 . Figure S1 outlines the results of the search process 31 …”
Section: Resultsmentioning
confidence: 99%
“…Table 1 summarized the key characteristics of the 15 included studies. Nearly 80% of the studies assessed the cost‐effectiveness of interventions based on topical fluoride therapy and fissure sealants at school premises 16‐18,21,23‐25,27,29,30 . Only two studies reported preference‐based health outcomes, 19,28 while all but one 16 reported an Incremental Cost‐Effectiveness Ratio (ICER).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations